PENGEMBANGAN BAHAN AJAR BERBENTUK KOMIK PADA MATA PELAJARAN ILMU BANGUNAN GEDUNG (IBG) KELAS X SMK NEGERI 5 PADANG - 211-220 , Ifdhal (CIVED, 2013)
The type of this research was Research and Development (R & D) and the trials carried out at the Department of Building engineering class X SMK N 5 Padang. Object of this research was the development of teaching materials in the form of comic subjects IBG. Data collection instruments used in this research were pieces of expert validation, test sheets practicality by teachers and students, sheets effectiveness of learning materials in the form of student activity sheets observation and learning outcomes. Products and data analysis techniques used were described techniques, methods graphic, descriptive analysis. First, a description of the design of teaching materials comic form consists of five sections that cover, competency standards, basic competencies, learning objectives, content and evaluation. Second, the comic form of teaching materials have very high validity with an average of 86.47 experts. Third, the use of teaching materials were very practical form of comics with practical value by 80 teachers' responses (1st practitioner) and 76 (2nd practitioner). Fourth, the use of teaching materials in the form of comic implementation of effective learning by SBC was characterized by the observation of student activity that categorize well with the value of 85% and an increase in student learning outcomes IBG meaningfully in learning with the average value of the practicality of using a t-test correlated as thitung (17.64) > ttabel (2.09). Key words : teaching materials, comic, IBG vocational learning